Rooting Response of Juvenile Shoot Cuttings of Banana Shrub (Michelia figo) Under IBA Treatment - Nautiyal, S.; Prakash, Rakesh; Kumar, Niteesh (Indian Forester, 2015)
The present study was carried out to investigate the effect of chemical treatment (IBA) on rooting of banana shrub (Michelia figo). A significant variation at P<0.05 level was observed on mean rooting percentage in two concentrations. The per cent rooting and primary root numbers improved markedly upon application of higher concentrations. Maximum per cent rooting (60) was recorded in cuttings treated with IBA 4000 ppm followed by 45 per cent in IBA 2000 ppm. However, minimum (20) per cent rooting was discernable in untreated cuttings (cuttings treated with talcum powderonly) following the trend IBA 4000 ppm>IBA 2000 ppm>control. Primary root number was also maximum in the cuttings treated with IBA 4000 ppm.